Metal-organic frameworks (MOFs) and their derivatives as emerging biomaterials for the treatment of osteoarthritis - Liu, Yufu; Zhang, Hongwei; Chen, Tianyan; Xu, Chang; Bao, Xingfu (Frontiers in Pharmacology, 2024)
As a novel class of smart biomaterials with promising potentials, metal-organic frameworks (MOFs) are widely utilized in the field of biomedicine. Current researches indicate that the therapeutic strategies for osteoarthritis (OA) are highly limited to achieving symptom improvement and reducing both pain and inflammation. Together, the introduction of MOFs into the treatment of OA holds the potential to offer significant benefits. This is because MOFs not only have intrinsic biological activities, but also act as carriers to facilitate controlled drug delivery and prolong the duration in the management of OA. This paper presents a review of the recent studies that have explored the potential usage of MOFs as drugs or carriers in the treatment of OA, which also examines the progress of MOFs in tissue engineering for the treatment of OA. These studies are anticipated to not only enhance the comprehension of MOFs but also provide strong evidence in favor of their utilization in the treatment of OA.